Immunotherapeutic Strategies in Chronic Lymphocytic Leukemia: Advances and Challenges - Perutelli, Francesca; Jones, Rebecca; Griggio, Valentina; Vitale, Candida; Coscia, Marta (Frontiers in Oncology, 2022)
Immune-based therapeutic strategies have drastically changed the landscape of hematological disorders, as they have introduced the concept of boosting immune responses against tumor cells. Anti-CD20 monoclonal antibodies have been the first form of immunotherapy successfully applied in the treatment of CLL, in the context of chemoimmunotherapy regimens. Since then, several immunotherapeutic approaches have been studied in CLL settings, with the aim of exploiting or eliciting anti-tumor immune responses against leukemia cells. Unfortunately, despite initial promising data, results from pilot clinical studies have not shown optimal results in terms of disease control - especially when immunotherapy was used individually - largely due to CLL-related immune dysfunctions hampering the achievement of effective anti-tumor responses. The growing understanding of the complex interactions between immune cells and the tumor cells has paved the way for the development of new combined approaches that rely on the synergism between novel agents and immunotherapy. In this review, we provide an overview of the most successful and promising immunotherapeutic modalities in CLL, including both antibody-based therapy (i.e. monoclonal antibodies, bispecific antibodies, bi- or tri- specific killer engagers) and adoptive cellular therapy (i.e. CAR-T cells and NK cells). We also provide examples of successful new combination strategies and some insights on future perspectives.